Penerapan Tata Kelola Keuangan Pada Koperasi Serba Usaha Werdhi Sedana Desa Baha Kecamatan Mengwi - Ni Kadek Yeni Dwi Putri; I Wayan Sudiana; Kadek Dewi Padnyawati (Hita Akuntansi dan Keuangan, 2025)
Family values are the cornerstone of the cooperative movement, which is a people's economic movement. The framework and procedures used to decide on a company's course and level of oversight are known as governance. The purpose of this thesis is to clarify or characterize the financial governance practices used by the Mengwi District's Baha Village Cooperative. This study employs qualitative research methodology, gathering data via observation, interviews, and documentation. The Werdhi Sedana Cooperative's management is the research's informant. The study's findings support the following conclusion: Werdhi Sedana Cooperative has done a good job of maximizing governance through the application of transparency, accountability, responsibility, independence, and justice by offering excellent service, growing cooperatives, assigning employees according to their roles, sharing information, and offering members training. There are challenges facing the Werdhi Sedana Cooperative from both inside and outside the organization that hinder the wellbeing of its members. By providing administrators and members with training, as well as by reaching out to members to better understand cooperatives, the Werdhi Sedana Cooperative should aim to optimize governance.